Alienation in corporate America: Fact or fable? - Saunders, Charles B. (Journal of business ethics, 1986)
Using NORC annual survey data, the authors selected 21 questions describing respondent attitudes toward job, life in general, and financial status. Respondents were catigorized as management, white collar, blue collar, and those not affiliated with business organizations. Attitudes were compared across the four occupational groups. Little dissatisfaction was found in any but the blue collar group. Management as a group, and men as well as women managers showed high levels of satisfaction, with few significant differences found in responses by men and women. This study does not support the earlier finding of widespread alienation in business firms.